MANAGEMENT ACCOUNTING OF INNOVATION COSTS - U. Blinova; D. Rozhkova; N. Rozhkova (Вестник университета)
The article substantiates the necessity of developing a management accounting of costs for innovation activity, which includes certain components, such as purpose, nature, types, stages, participants and resources. The link of management accounting and innovation activity is given, stages of the process of cost accounting on a targeted basis are outlined. Cost centers and centers of responsibility for innovation have been developed. Authors propose the classification of costs for each innovative project by cost items. The form of account and analysis of innovative costs according to elements of costs is presented.